2017
DOI: 10.18632/oncotarget.23455
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes released by metabotropic glutamate receptor 1 (GRM1) expressing melanoma cells increase cell migration and invasiveness

Abstract: Exosomes are naturally occurring membrane-bound nanovesicles generated constitutively and released by various cell types, and often in higher quantities by tumor cells. Exosomes may facilitate communication between the primary tumor and its local microenvironment, supporting cell invasion and other early events in metastasis. A neuronal receptor, metabotropic glutamate receptor 1 (GRM1), when ectopically expressed in melanocytes, induces in vitro melanocytic transformation and spontaneous malignant melanoma de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Suppressive effects of riluzole on GRM1 þ melanoma cell proliferation were reported earlier (17,39,40). Here, the consequences of including both CB-839 and riluzole on cell growth of two GRM1-expressing human melanoma cell lines were investigated.…”
Section: Combinatorial Treatment With Cb-839 and Riluzole Leads To Enmentioning
confidence: 70%
“…Suppressive effects of riluzole on GRM1 þ melanoma cell proliferation were reported earlier (17,39,40). Here, the consequences of including both CB-839 and riluzole on cell growth of two GRM1-expressing human melanoma cell lines were investigated.…”
Section: Combinatorial Treatment With Cb-839 and Riluzole Leads To Enmentioning
confidence: 70%
“…They share many antigens with vascular endothelial cells (vasculogenic mimicry) which enables them to survive in the circulation, and increases their migration and invasion capacity as well. Furthermore, melanoma-derived extracellular vesicles also have a crucial role in the rapid tumour progression 812 . They are capable to induce a tumour-favourable phenotype in the EV-recipient cells in the TME 13 and the metastatic sites 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Our lab demonstrated that inhibition of mGluR1 expression or function by genetic or pharmacological inhibitors in melanoma cells, did not modulate the number of exosomes released, but rather reduced the functions of the exosomes on the recipient cells in cell migration, invasion, and anchorage-independent growth, perhaps through cargo sorting into exosomes [357].…”
Section: Exosomesmentioning
confidence: 85%